International Construction Joint Ventures as a Resourcing Model - Chao, Q; Rotimi, FE; Rotimi, JOB (Thomas Telford, 2021)
Shortages in materials, skilled labour and equipment are well known within construction industries, and impede performance on ongoing and pipeline projects. This study explores international construction joint ventures (ICJVs) as a resourcing model that could relieve pressures within the New Zealand (NZ) construction industry. The study goes further to identify the risks and constraints associated with ICJVs. There is a dearth of literature on the role of ICJVs and their impact on the industry within the context of resource acquisition. The data for this study were collected by way of the administration of an online questionnaire survey to a representative sample of contractors, developers and consultants. A simple descriptive method of analysis was employed for ease of understanding. The study established that materials and labour were the most demanding resources that ICJVs could help address in NZ. Risks associated with compliance with local regulations and certification requirements and those related to lead times were the most critical constraints for international material acquisition. The study findings also indicate that language and communication barriers and differences in the practice of rules and regulations were the most significant constraints for utilising international skilled labour.
Keywords: Construction; International joint ventures; New Zealand resourcing